(untitled) (Future Cities and Environment, 2024)
The notions of Performance and Performative are emerging in architectural design discourses including heritage processing and repurposing. The literature review shows that the terms are semantically wide and they are linked to a variety of concepts: the open form, the flexible, the dynamic, the event—based spatial settings and the active engagement with space. The essay examines how – beyond museumification -the activation and the reuse of heritage sites can be seen through the lens of Performance and the concept of the Performative, and the difference between passive engagement and active engagement. The essay has three folds aims unfolding as follow: The first explores a literature review analysis of Performative and Performance in architectural discourse, arriving to explore those concepts in the discourses of reuse of historical heritage sites as exhibitions performative venues. The second examines a proposed performative-oriented approach to the reuse of heritage sites which aims at a dynamic and active engagement with the space, opposing to museumification which usually leads to passive engagement while taking examples from Europe. The third one will be centered on the case of the old heart of Sharjah in the United Arab Emirates as a heritage site reinvented and inhabited by the Sharjah Art Foundation, which we will analyze through the lens of the Performative and the practice of Exhibiting.